PENGARUH RATIO ASAM OLEAT – SORBITOL PADA PRODUK SORBITAN MONOOLEAT MELALUI PROSES ESTERIFIKASI - Anah, Lik (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2007)
The synthesis of sorbitan monooleat was conducted at laboratorium scale by es-terification of sorbitol and oleic acid using p-toluene sulfonic acid as catalyst. The esterifi-cation process was carried out at operation condition : atmospheric pressure; stirred; 7 hours of reaction; 180oC and concentration of catalyst 2.5 % based on sorbitol. The ratio of oleic acid – sorbitol concentration used in this experiment was varried at 0.75; 1.0; 1.25 and 1.50. A sample was drawn off every 10 minutes during the first hour reaction and e-very 30 minutes during the next six hours. The analysed of sample was conducting by de-termining acid value to calculate the sorbitan monooleat product. The result of the experi-ment showed that the optimum ratio of oleic acid - sorbitol was reached at 1.0 with sorbi-tan monooleat production of 72.939 % in 60 minutes with acid value 46.132 and 82.93-5 % in 420 minutes with acid value 30.909.